Formulasi Strategi di Kalangan Syarikat-Syarikat Penerbangan Nasional Indonesia : Satu Kajian Kes - Rosyadhi, M. Fathur Rahman (2005)
Successfully maintaining the operations of airline companies is a strategic problem that requires a strategic management process which begins with strategy formulation prior to its implementation. The purpose of this study was to examine critically the strategic management among the national airline companies in Indonesia. More specifically, this study attempted to analyse the models for the formulation of strategies that were used by airline companies in Indonesia. This study employed the case study method, which involved six airlines that were almost scheduled airline companies in Indonesia. They consisted of four airlines (i.e. Garuda, Merpati, Mandala dan Bouraq) with long years of experience since the 1970s, and two newly formed airlines (i.e. Pelita Air and Star Air), which started operations and scheduled flights in the year 2000. The results of the study revealed that strategy was ranked third amongst nine items of importance in the strategic management of scheduled airline companies in Indonesia, where the first ranked item was considered the most important. There were three scheduled airline companies which practised the strategy formulation model developed by David, while the other companies used other models or methods, such as the Balanced Scorecard, Sun Tim, Hitt, Mintzberg and Canvas, as a basis for formulating their strategies. According to the five airline companies, there was no specific strategic formulation model that can be used for the airline industry in Indonesia. All of the airline companies in this case study used SWOT analysis for auditing purposes. Other technical analyses employed included the BCG matrix, the TOWS matrix and the Competitive Profile matrix. The six airline companies indicated that they would continue to use SWOT analysis, and five of them had stated that SWOT analysis would not be replaced.